Utilization of intestinal organoid models for assessment of micro/nano plastic-induced toxicity - Yuan, Qinqin; Liu, Yajing (Frontiers in Environmental Science, 2023)
Micro/nano plastics (M/NPs) are emerging pollutants that have extensively infiltrated various aspects of human life, posing a significant threat to the natural ecological systems. M/NPs can enter the digestive system through the oral cavity and accumulate in various organs. The current research on M/NPs primarily relies on model organisms, and there remains a dearth of direct evidence concerning the impact of M/NPs on human health. Commonly utilized specific two dimensional (2D) cultured cell lines exhibit substantial disparities in physiological functions when compared to multicellular tissues in vivo. The conduct of animal experiments is a time-consuming process, constrained by ethical considerations, and also confronted with interspecies variations. A significant breakthrough in biology is the development of organoids derived from stem cells. Intestinal organoids can mimic the complex structure and functionality of tissue, and can generate cell-cell and cell-matrix interactions that closely resemble physiological responses in the body. As a result, they provide a more accurate reflection of toxic effects and mechanisms, and hold great potential for applications in the environmental toxicology assessment. However, the current research on the toxic mechanisms of M/NPs using intestinal organoids is still in its early stages. The focus of this review is on the application of intestinal organoids in toxicology studies of M/NPs, assessing the correlation between M/NPs and diseases, as well as elucidating the molecular mechanisms underlying toxic effects. Ultimately, we present the challenges and potential solutions for utilizing intestinal organoids as models to evaluate M/NPs-induced toxicity, aiming to provide valuable insights for future research.